ANALISIS DAMPAK ENSO (EL-NINO SOUTHERN OSCILLATION) TERHADAP TINGKAT KEKERINGAN UNTUK TANAMAN PANGAN DAN PALAWIJA (STUDI KASUS : SULAWESI SELATAN) - Yon Sugiarto; Dori Kurniawan (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2009)
Weather and climate variability is a long-term weather changes that are characterized by fluctuations and deviations from normal conditions. One possible cause is the ENSO (El-Nino Southern Oscillation) which affected in drought events. This research was conducted to determine and analyze the level of drought in South Sulawesi due to the influence of ENSO and compare the production of food crops and secondary food crops in normal years and ENSO.Drought index is calculated based on the Palmer method by using data of rainfall, air temperature and soil moisture as input. Based on the calculations using the method of Palmer drought index, the regions with monsoon rain patterns have a range of values between -22.71 drought until 18:23, Equatorial patterns ranging from -4.03 to 5:07, and on local patterns rangedfrom -8.57 until 10:07. Verification test results on the drought index of crop production data showed that each ENSO event is always followed by a decline in rice production, especially of rice fields. Food crop production generally tends to increase at each ENSO event because most crops are plants that are resistant to drought, particularly local varieties that have adapted well to their environment. Thus, the drought caused by the influence of ENSO can affect the production of food crops and secondary food crops.